2019
DOI: 10.1002/admi.201900291
|View full text |Cite
|
Sign up to set email alerts
|

Caloric Effects in Perovskite Oxides

Abstract: Perovskite oxides show an amazing diversity of electronic and magnetic properties along with a myriad of structural variants and phase transitions. Large thermal changes may be driven near the ferroic phase transitions in perovskite oxides using magnetic, electric, and stress fields to manipulate conjugate order parameters. The ensuing magnetocaloric, electrocaloric, and mechanocaloric effects can be utilized for environment‐friendly and high‐efficiency solid‐state cooling applications. In this review the deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 421 publications
0
34
0
Order By: Relevance
“…4b , we compare PST’s η mat with η mat of the MC material Gd (Supplementary Note 7 ) calculated in an equivalent way. Although Gd exhibits a second-order phase transition contrary to PST, it is of interest to compare their materials efficiency because they are both considered the benchmark materials of their respective caloric family 3 . Hence, we computed direct values of η mat of Gd from the data in Bjork et al 23 using the formalism of Heine 24 , already used by Moya et al 8 to extract η mat of MC materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4b , we compare PST’s η mat with η mat of the MC material Gd (Supplementary Note 7 ) calculated in an equivalent way. Although Gd exhibits a second-order phase transition contrary to PST, it is of interest to compare their materials efficiency because they are both considered the benchmark materials of their respective caloric family 3 . Hence, we computed direct values of η mat of Gd from the data in Bjork et al 23 using the formalism of Heine 24 , already used by Moya et al 8 to extract η mat of MC materials.…”
Section: Resultsmentioning
confidence: 99%
“…Fridges and air conditioning consume fifteen percent of the world’s energy 1 . Looking for an alternative to the almost exclusively used vapor compression system is a crucial technological challenge as one needs to suppress the use of greenhouse gases and improve energy efficiency as much as possible 2 , 3 . Recent findings have demonstrated that electrocaloric (EC) devices represent a more and more credible alternative 4 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite materials (ABX 3 ) including oxide-perovskite and halide-perovskite are a special kind of inorganic film, whose special characteristic comes from its unique properties. The most remarkable feature is that it can produce a photothermal effect, which means that the conversion of light and electricity in the environment can be realized through these films [107,108] [111].…”
Section: Complex Metal Oxidesmentioning
confidence: 99%
“…However, the limited potential of vapor compression leads us back to the search for alternative electrically or mechanically driven systems. Several researchers have concluded that caloric (ferroic) refrigeration and heat‐pumping technologies, which are still in the research and development phase, are the most important option for the future . These solid‐state technologies variously utilize magnetocaloric, electrocaloric, and mechanocaloric effects.…”
Section: Introductionmentioning
confidence: 99%